(untitled) (Revista de Estudos da Linguagem, 2024)
In this article, we address the adjective in contemporary Brazilian Portuguese. We aim to analyze this linguistic category in a constructionist account considering morphological, syntactic, semantic, cognitive and discursive-pragmatic aspects involved in its use. Our approach is qualitative-explanatory in nature with eventual quantitative support. In the analysis, we use speech and writing data collected in different discursive genres, seeking to capture the multifunctionality of the adjective in communicative interaction. The study is theoretically and methodologically supported by Usage-based Functional Linguistics, a current that articulates in its investigations operational assumptions and concepts of North American Functional Linguistics and mainly of Construction Grammar. Data from the corpus show that formal and functional diversity of adjective constructions is motivated most of all by cognitive and discursive-pragmatic factors.